Experience of Intra-University Cooperation in the Process of Creating Professionally-Oriented Foreign Language Textbooks - N. V. Popova; N. I. Almazova; T. G. Evtushenko; O. V. Zinovieva (Высшее образование в России)
The article discusses the creation of professionally-oriented foreign language textbooks in the process of interaction between the department of foreign languages and the specialized departments of a technical university. Inter-departmental cooperation is considered as a university resource for improving the quality of higher education; examples of successful interdepartmental cooperation at the Peter the Great St. Petersburg Polytechnic University are given. It is shown that a characteristic feature of a professionally-oriented textbook of the new generation, created by the joint efforts of the linguistic and specialized departments is the widespread use of the elements of the computer-based learning environment, which contributes to a more effective mastering of the subject content. A list of seven English language textbooks created as a result of inter-departmental cooperation, and a brief analysis of the problems that arose in the process of communication between specialists of linguistic and technical profiles are presented. It is shown that the process of creating foreign language textbooks can be simultaneously used as a practice-oriented interdisciplinary project for master degree students of a linguistic profile who participate in it as developers of the linguistic content of these textbooks. Participation of the postgraduates in this project is supported by the curricular discipline “Interdisciplinary links in higher education” and teaching practice.